Nurse’s Roles in Protecting Cancer Patients During COVID-19 Pandemic - Siluh Nyoman Alit Nuryani; Luh Gede Lisnawati (Program Studi Ilmu Bedah, Fakultas Kedokteran Universitas Udayana, 2020)
Nurses during COVID-19 pandemic outbreak will be front line health care worker providing care for all patient including cancer patients. Cancer patients were vulnerable group that need to be prevented from getting COVID-19. This study will describe the roles of nurses to protect cancer patients during this outbreak. The role of nurses preventing transmission in outpatient including conducting medical distancing to reduce number of patient visit health care. This can be done through screening by phone. Chemotherapy unit, nurses can prevent transmission through physical distancing, providing education and surface cleaning more often than usual in between patient. Oncology ward, nurses need to educate patient family regarding no hospital policy visit. This will reduce number of exposure people to people. The use of PPE wisely due to shortage of resources in may hospital facilities by reducing number of team member entering patient’s room, selectively usage of PPE required for certain nursing procedures, and nurses can perform number of procedures at once whenever nurses enter patients’ room. During this crisis, nurses also need to maintain their mental health by managing their stress and anxiety by balancing between work and rest during shifts, eat sufficient food and healthy, and avoid alcohol and tobacco. Stay connected with friends and family through digital media. Hence, nurses can stay healthy so they care for patients during this pandemic.